1992
DOI: 10.1007/bf00174465
|View full text |Cite
|
Sign up to set email alerts
|

Growth and sporulation behaviour of Penicillium roquefortii in solid substrate fermentation: effect of the hydric parameters of the medium

Abstract: Both growth and sporulation increase linearly according to the initial water content of the solid substrate when Penicillium roquefortii is cultivated on buckwheat seeds. This indicates that water is the limiting factor for fungal development since neither carbon nor nitrogen sources were exhausted during these experiments. This feature validates the concept of available water for fungal growth, defined as initial water content of substrate minus its residual water content when vegetative growth stops. An effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 17 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…10). However, it should be noted that the moisture content of the solid substrate itself during fermentation is probably lower than the measured overall moisture content, because biomass, as part of the wheat grain, probably has a higher moisture content than the overall average (Larroche et al, 1992;Oriol et al, 1988).…”
Section: Effect Of Evaporative Coolingmentioning
confidence: 99%
“…10). However, it should be noted that the moisture content of the solid substrate itself during fermentation is probably lower than the measured overall moisture content, because biomass, as part of the wheat grain, probably has a higher moisture content than the overall average (Larroche et al, 1992;Oriol et al, 1988).…”
Section: Effect Of Evaporative Coolingmentioning
confidence: 99%
“…Previous studies have shown that fungal development can cease when the water content is below a certain threshold value. Lesions of Phytophthora cinnamomi on stems of Eucalyptus marginata ceased their extension when the relative water content was <85% (33), and mycelial growth and sporulation of Penicillium roquefortii on buckwheat seeds ceased when the relative water content was close to 40% (18). In studies on fungal growth in alfalfa hay the threshold relative water content for ascoma development (28 to 42%) was lower than that for mycelial development (52 to 65%) of fungi in the hay (2).…”
Section: Discussionmentioning
confidence: 96%
“…The suspension was diluted in sterile water and the concentration of spores was determined using a Malassez chamber. 11 Concentration was expressed in terms of the number of spores g −1 dry CP.…”
Section: Spore Production Measurementsmentioning
confidence: 99%